The Role of Husband and Wife in Child Care From Islamic Law Perspectives - Minhar Minhar; Zainal Zainal; Hilal Malarangan (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2020)
This paper discusses the role of husband and wife in child care from Islamic perspective. This study uses qualitative methods and data was gathered through observation, in-depth interviews, and written material. Data analysis was analyzed using grounded theory approach. The results show that parenting activities in the village of Tinggede are not only about rising children, but also about educating, guiding, and protecting children from childhood to adulthood in accordance with Islamic values, norms and culture. The parents expect their children can grow and develop naturally, harmony, and balance based on Islamic teaching. Parenting in Islamic law (hadhanah) is a responsibility of both parents who must get special attention from their parents in particular during childhood period. The authors conclude that parents should accompany their children with Islamic values and norms to inculcate religious behavior of their children.